Pelatihan Penyusunan Jurnal Penyesuaian bagi Siswa/I SMP: Penguatan Pemahaman Siklus Akuntansi dan Penyusunan Laporan Keuangan - Amin Wijoyo; Richard Edbert; Stewart Sebastian (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2026)
Understanding adjusting entries is one of the fundamental competencies that students should acquire in learning the accounting cycle, as it plays an important role in the preparation of financial statements in accordance with accounting principles. However, at the junior high school level, as observed at Kristen Yusuf Junior High School Jakarta, many students still experience difficulties in understanding the concept of adjusting entries, identifying accounts that require adjustments, and recognizing their impact on financial statements. These challenges are caused by limited instructional time, insufficient opportunities for practical exercises, and teaching methods that remain focused on theoretical instruction. Therefore, the Faculty of Economics and Business at Tarumanagara University conducted a Community Service Program (PKM) aimed at providing students of Kristen Yusuf Junior High School Jakarta with a deeper understanding of adjusting entries. The program was carried out through interactive face-to-face learning sessions, accompanied by discussions of relevant case studies. This Community Service Program is expected to serve as an alternative approach to accounting education by promoting more interactive learning, enhancing students' understanding of adjusting entries, and strengthening their foundational knowledge of the accounting cycle and the preparation of financial statements.